The Association of Sodium-Glucose Cotransporter-2 Inhibitors With Improved Clinical Outcomes in Heart Failure: A Systematic Review of Landmark Clinical Trials - Anggreini Oktavia Trisno; Chelsia Ernes (International Medical Journal Corp. Ltd, 2025)
Introduction: Heart failure (HF) represents a major global health burden characterized by significant morbidity, mortality, and healthcare expenditure. While established therapies exist for HF with reduced ejection fraction (HFrEF), effective treatments for HF with preserved ejection fraction (HFpEF) have been elusive. Sodium-glucose cotransporter-2 (SGLT2) inhibitors, initially developed as anti-hyperglycemic agents, have emerged as a transformative therapeutic class for HF. This systematic review synthesizes the evidence from landmark clinical trials on the efficacy and safety of SGLT2 inhibitors in improving HF outcomes. Methods: A systematic search of major electronic databases PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted to identify large-scale, randomized, double-blind, placebo-controlled trials evaluating SGLT2 inhibitors in patients with HF or those at high risk for HF. Key efficacy outcomes included the composite of cardiovascular (CV) death or hospitalization for heart failure (HHF), its individual components, all-cause mortality, total HHF, renal outcomes, and changes in quality of life. The methodological quality of included trials was assessed using the Cochrane Risk of Bias tool. Results: Sixteen landmark clinical trials and two major meta-analyses were included, encompassing a diverse population of patients with and without type 2 diabetes (T2DM) across the full spectrum of left ventricular ejection fraction (LVEF). The evidence demonstrates a consistent and robust class effect. SGLT2 inhibitors significantly reduce the primary composite outcome of CV death or HHF by approximately 20-25% across all HF phenotypes. This benefit is predominantly driven by a substantial reduction in the risk of first and total HHF, observed in HFrEF (Hazard Ratio ), HFpEF (HR ), and in patients with recent worsening HF. A significant reduction in CV death and all-cause mortality was established in patients with HFrEF, with large meta-analyses suggesting a modest mortality benefit across the broader HF population. Furthermore, SGLT2 inhibitors consistently demonstrated profound nephroprotective effects and led to clinically meaningful improvements in patient-reported symptoms and quality of life. The safety profile was generally favorable and consistent across trials. Discussion: The consistent benefits observed across a wide range of patient populations, irrespective of baseline LVEF or diabetes status, have fundamentally altered the HF treatment paradigm. The pleiotropic mechanisms of SGLT2 inhibitors, including hemodynamic, metabolic, and direct myocardial effects, likely contribute to these favorable outcomes. Conclusion: SGLT2 inhibitors have unequivocally been established as a foundational pillar of guideline-directed medical therapy for HF. They significantly reduce the burden of HF hospitalizations, slow the progression of concomitant kidney disease, improve quality of life, and, in HFrEF, reduce mortality.